Analysis of interest factors for entrepreneurship of accounting education students - Pamungkas, Noviyan Bhekti; Utomo, Supri Wahyudi; Yusdita, Elana Era (Jurnal Entrepreneur dan Entrepreneurship, 2020)
This study aims to determine the various factors that become the interest in entrepreneurship in accounting education students at Universitas PGRI Madiun. This study used a qualitative approach and the type of research was descriptive. The researcher conducted interviews with informants, namely accounting education students at the Universitas PGRI Madiun. The results of this study are that the informants R, Y, T, K and P are interested in entrepreneurship, but the informant (R) has an introverted personality. Then for the informant (P), the poor learning achievement factor did not become an obstacle in him being interested in entrepreneurship, another uniqueness was found, namely that the informant (K) did not have support from friends and had little leadership. For this reason, it is suggested to have leadership training, public speaking and entrepreneurship skills for students.